KELAS INTERAKTIF IBU SEBAGAI UPAYA PENINGKATAN PEMAHAMAN TENTANG PERTUMBUHAN DAN PERKEMBANGAN BAYI DAN BALITA DI DUSUN BINTARAN KULON PIYUNGAN BANTUL - Endah Tri Wahyuni (LPPM STIKES Madani Yogyakarta, 2019)
The golden age period is a period in which a child's brain develops very rapidly and absorbs information most quickly. The golden period is a very vital period or something very important in a cycle. The golden period in children is an important period during which the child's brain or intelligence is very rapidly developing. Based on the servant's observations, some mothers in the Bintaran Kulon area still lack knowledge regarding the growth and development of babies and toddlers. Therefore, pengabdi tries to create an interactive class as a place for parents to pay attention to the development and growth of their children.. The model approach used to solve this problem is by approaching the community, especially mothers who have babies and toddlers. The method used is lectures, questions and answers and direct simulation in the implementation of growing back infants and toddlers.